Protective capacity of an ice hockey goaltender helmet for three events associated with concussion. Issue 12 (10th September 2017) - Clark, J. Michio; Hoshizaki, T. Blaine; Gilchrist, Michael D.
Abstract: The purpose of this study was to assess the protective capacity of an ice hockey goaltender helmet for three concussive impact events. A helmeted and unhelmeted headform was used to test three common impact events in ice hockey (fall, puck impacts and shoulder collisions). Peak linear acceleration, rotational acceleration and rotational velocity as well as maximum principal strain and von Mises stress were measured for each impact condition. The results demonstrated the tested ice hockey goaltender helmet was well designed to manage fall and puck impacts but does not consistently protect against shoulder collisions and an opportunity may exist to improve helmet designs to better protect goaltenders from shoulder collisions.